2011
DOI: 10.1039/c0cp02250k
|View full text |Cite
|
Sign up to set email alerts
|

Non-reactive scattering of N2 from the W(110) surface studied with different exchange–correlation functionals

Abstract: The non-reactive scattering of N 2 from the W(110) surface is studied with six dimensional (6D) classical dynamics and two distinct potential energy surfaces (PES). Here, we use the PESs calculated with density functional theory and two different exchange-correlation functionals, the PW91 In general, the PW91 PES is more corrugated than the RPBE one in all the configurational space, meaning that there is a stronger dependence of the potential energy on the molecular orientation and position over the surface un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…The authors concluded that the PW91-PES is less accurate close to the surface, in the area where the dissociation takes place, while the RPBE-PES is too repulsive at larger distances from the surface. A similar conclusion concerning the RPBE-PES was obtained from a comparison of non-reactive scattering simulations to experiments, which also suggested that the PW91-PES is too corrugated [19].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The authors concluded that the PW91-PES is less accurate close to the surface, in the area where the dissociation takes place, while the RPBE-PES is too repulsive at larger distances from the surface. A similar conclusion concerning the RPBE-PES was obtained from a comparison of non-reactive scattering simulations to experiments, which also suggested that the PW91-PES is too corrugated [19].…”
Section: Introductionsupporting
confidence: 56%
“…Tungsten surfaces, among others, have received much attention [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], with particular focus on the large crystallographic anisotropy that this metal exhibits with respect to nitrogen adsorption. For instance, the thermal reactivity of W(100) is about two orders of magnitude larger than the W(110) reactivity [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is at this stage when nowadays simulations based, mostly, on density functional theory (DFT) are the necessary counterpart to fully understand the properties governing these processes and to confirm the interpretation of the experimental outcome. 4,[11][12][13] In this respect, there are various examples showing that not only the reactivity [14][15][16] but also scattering properties such as the diffraction peaks positions, 17,18 angular distributions, [19][20][21][22][23] rotational states, [24][25][26][27][28] and energy loss 21,23,29 are reasonably described by this level of theory. Considering that in all these cases, the potential energy surfaces (PESs) have been calculated with the (hitherto standard) semilocal exchange-correlation (xc) functionals that do not correctly describe the long-range van der Waals (vdW) interaction, such an agreement is somehow unexpected at first thoughts.…”
Section: Introductionmentioning
confidence: 97%
“…37 The same conclusion was later on obtained when comparing the rovibrational energy of the scattered molecules with available experimental data. 26 Motivated by all these previous results that pinpoint the significance of the N 2 -W(110) large distance region, our purpose here is to determine the relevance of the vdW interaction in the dissociative dynamics of N 2 on W(110). To this aim, we perform ab initio molecular dynamics (AIMD) calculations within the Born-Oppenheimer approximation (BOA) using a selection of the existing vdW-functionals.…”
Section: Introductionmentioning
confidence: 99%
“…27) or rotational state distributions of N 2 molecules scattered from W(110). 28 Non-adiabatic 6D dynamics calculations, based on electronic friction coefficients computed with density functional theory (DFT) using different approximations, show that within this approach, e-h pair excitations play a minor role in the dissociative adsorption of H 2 on Cu(110), N 2 on various tungsten surfaces, and O 2 on Pd(100). 22,29,30 A similar conclusion has been recently reached for the scattering of N 2 from W(110) and N from Ag(111).…”
Section: Introductionmentioning
confidence: 99%